Impact of the ‘Barkada Kontra Droga Program’ on Student Awareness of Illegal Drugs - Soriano, Jaime (Journal of Interdisciplinary Perspectives, 2025)
This study explored the effects of the BKD program in enhancing the level of awareness of senior high school students from Cambaog National High School (CNHS) about the ill effects of prohibited drugs through symposiums, school-based contests, and culminating activities. Participants were 60 students from the senior high school department of Cambaog National High School and 10 representatives from the Department of Education (DepEd), Local Government Units (LGU), Bustos Municipal Police Station (MPS), and Bustos Local Youth Development Office (LYDO). Before the program's implementation, student participants were given a pretest to assess their baseline knowledge about illegal drugs (M=2.72, SD=1.41, N=60). After the program's implementation, the student-respondents were asked to take a posttest and conduct culminating activities to determine the new skill sets or knowledge that transpired after the program's implementation. Results suggested that the BKD program aided in improving the student- respondent’s knowledge about the ill effects of prohibited drugs as evidenced by enhanced posttest scores (M=3.96, SD=0.81, N=60) and very high culminating activity ratings given by the representatives from the DepEd, LGU, Bustos PNP, and Bustos LYDO (M=3.67, SD=0.68, N=10).